Effects of testosterone administration and gonadectomy on incentive downshift and open field activity in rats - Justel, Nadia (2012)
Previous research showed that the effects of incentive downshift in male rats are attenuated by a pretrial opportunity to ejaculate. Because ejaculation raises testosterone (T) levels and has anxiolytic-like effects in male rats, the present experiments were designed to assess the role of T and gonadectomy (GDX) on two situations involving incentive downshift. In consummatory successive negative contrast, a downshift from 32% to 4% sucrose leads to consummatory suppression. T alleviates such suppression (Experiment 1), but GDX does not affect it (Experiment 3). In consummatory extinction, animals are downshifted from 32% sucrose to an empty sipper tube. T enhances consummatory extinction (Experiment 2), but GDX does not affect it (Experiment 4). In agreement with published results, T increases (Experiment 2) and GDX reduces (Experiment 4) activity in the central area of an open field, thus behaviorally validating these manipulations. The results are discussed in terms of the anxiolytic-like properties of androgen hormones. © 2012 Elsevier Inc.